1. Economic Analysis Between Two Different Systems Of Goat Farming Business In Asahan District, North Sumatera - Supardi Rusdiana; Rijanto Hutasoit; Juniar Sirait (The International Journal of Tropical Veterinary and Biomedical Research, 2016)
The study was conducted in the Tinggi Raja village and Sumber Harapan Village of Sub district Tinggi Raja, in the Asahan District. Each location study has the same agro-ecosystems. The study was conducted using survey method in year of 2013 by interviewing 15 farmers respondent as cooperators and 15 non-cooperators. Primary data and secondary data were analyzed economically, using descriptive and quantitative tabulation. The purpose of this study was to determine the increase in business of goat breeders for economic analysis. The results showed that the net profit of the business of goats in cooperators breeders at the amount of Rp.8.411.168,83/year, B/C ratio of 1.4. Then for the non-cooperator farmers at the amount of Rp.1.644.051.24/year, B/C ratio of 1.2. This data showed that the benefit of farmer cooperators is higher than the non cooperator breeders. Therefore we need to implement the introduction of technological innovations for the farmer in non-cooperators breeders. For cooperators they could get into commercial business, that resulted in their goats achieving a higher market value in terms of price.